The selective dopamine D3 receptor antagonist, SR 21502, reduces cue-induced reinstatement of heroin seeking and heroin conditioned place preference in rats - Galaj, Ewa (Drug Alcohol Depend, 2015)
BACKGROUND: Because the role of dopamine (DA) D3 receptors has been investigated primarily in relation to cocaine-related behaviors little is known of the role of these receptors in heroin seeking. PURPOSES: To investigate the effect of the selective DA D3 receptor antagonist, SR 21502, on cue-induced reinstatement of heroin seeking and heroin conditioned place preference (CPP). METHODS: In experiment 1, rats were trained to self-administer intravenous heroin for 15 days followed by extinction. Following extinction animals were treated with one of several SR 21502 doses (0, 7.5, 10 or 15 mg/kg) and a cue-induced reinstatement test was conducted. In Experiment 2, animals were conditioned to experience heroin in one compartment of a CPP apparatus and saline in the other. On the test day animals were treated with 0, 3.75, 7.5, 10 or 15 mg/kg of SR 21502 and tested for their CPP. RESULTS: The results from Experiment 1 showed a significant dose-related reduction in cue-induced reinstatement of active lever pressing in the 7.5 and 10 mg groups and an absence of the reinstatement effect in the 15 mg group. In experiment 2, animals treated with vehicle or 3.75 mg of SR 21502 showed significant heroin place preferences but those treated with the higher doses showed no CPP. CONCLUSIONS: Our findings suggest that DA D3 receptors play a significant role in heroin approach behaviors driven by conditioned stimuli. As such, we propose that SR 21502 holds potential as an effective pharmacotherapeutic agent for relapse prevention and should be studied further.